2015
DOI: 10.1152/ajpcell.00220.2014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory role of REV-ERBα in the expression of bone morphogenetic protein gene family in rat uterus endometrium stromal cells

Abstract: Uterus circadian rhythms have been implicated in the gestation processes of mammals through entraining of the clock proteins to numerous downstream genes. Bone morphogenetic proteins (BMPs), having clock-controlled regulatory sites in their gene promoters, are expressed in the uterus during decidualization, but the regulation of the Bmp gene expression is poorly understood. The present study was designed to dissect the physiological roles of the uterus oscillators in the Bmp expression using the uterus endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…5B). The Bmp2 transcript, selected as a positive control, was also upregulated by SR8278 treatment, as previously reported (50). Concomitantly, the production of PGE 2 significantly increased at 24 h after treatment with the antagonist (P Ͻ 0.01 vs. CONT; Fig.…”
Section: Expression Levels Of Clock Genes and Ptgs2 In The Pregnant Rsupporting
confidence: 77%
“…5B). The Bmp2 transcript, selected as a positive control, was also upregulated by SR8278 treatment, as previously reported (50). Concomitantly, the production of PGE 2 significantly increased at 24 h after treatment with the antagonist (P Ͻ 0.01 vs. CONT; Fig.…”
Section: Expression Levels Of Clock Genes and Ptgs2 In The Pregnant Rsupporting
confidence: 77%
“…Meanwhile, BMAL1 regulation of TGF-β and BMP signaling in the control of fat adipogenesis has also been reported (27). a recent study showed that BMal1 silencing-induced BMP2 was found in rat uterus endometrium stromal cells (28). Samsa et al (5) recently reported that BMal1 -/mice had reduced osteoblast differentiation in vitro and they proposed some potential molecular mechanism of BMal1-dependent control of osteogenic differentiation including oxidative stress response, the mTor signaling pathway and translation.…”
Section: Discussionmentioning
confidence: 89%
“…The involvement of REV-ERBα was also implicated in the molecular control of decidualization. Evidence supports an inverse role of REV-ERBα on bone morphogenetic proteins (BMPs) in rat uterus endometrial stromal cells (UESCs); in Bmal1 siRNA-transfected UESCs, the Rev-erbα was downregulated and, consequently, Bmp2, Bmp4, and Bmp6 genes were upregulated [21]. The same investigators also observed that growth/differentiation factor (Gdf) 10 and 15 and prostaglandin G/H synthase 2 (Ptgs2), which are significantly increased during decidualization, were only upregulated after Rev-erbα was downregulated.…”
Section: The Uterine Biological Rhythm As a Target For Melatonin's Acmentioning
confidence: 99%
“…Sci. 2020,21, 300 11 of This figure illustrates possible mechanisms by which melatonin influences endometriosis (EMS). It is well-accepted that elevations in mitochondrial NAS/melatonin ratio, E2 levels, and ROS formation are associated with EMS development; other conditions like pinealectomy and circadian clock disruption are also reported to suppress melatonin which may possibly enhance the risk of EMS.…”
mentioning
confidence: 99%